2009
DOI: 10.1371/journal.pone.0004422
|View full text |Cite
|
Sign up to set email alerts
|

IrrE, a Global Regulator of Extreme Radiation Resistance in Deinococcus radiodurans, Enhances Salt Tolerance in Escherichia coli and Brassica napus

Abstract: BackgroundGlobally, about 20% of cultivated land is now affected by salinity. Salt tolerance is a trait of importance to all crops in saline soils. Previous efforts to improve salt tolerance in crop plants have met with only limited success. Bacteria of the genus Deinococcus are known for their ability to survive highly stressful conditions, and therefore possess a unique pool of genes conferring extreme resistance. In Deinococcus radiodurans, the irrE gene encodes a global regulator responsible for extreme ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
97
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 54 publications
13
97
2
3
Order By: Relevance
“…d IR, ionizing radiation; ϩϩ, high level of postirradiation induction; ϩD or ϩϩD, induction after ionizing radiation and desiccation. (479,681). Another novel stress response transcriptional regulator, DrRRA, regulates the expression of numerous genes under normal and ionizing radiation conditions, such as DNA damage-related genes (e.g., recA, pprA, ligT, cinA, gyrB, and uvrB), dps1, genes homologous to plant desiccation resistance proteins, and genes for antioxidant proteins, chaperones, and proteases (645).…”
Section: Continued On Following Pagementioning
confidence: 99%
“…d IR, ionizing radiation; ϩϩ, high level of postirradiation induction; ϩD or ϩϩD, induction after ionizing radiation and desiccation. (479,681). Another novel stress response transcriptional regulator, DrRRA, regulates the expression of numerous genes under normal and ionizing radiation conditions, such as DNA damage-related genes (e.g., recA, pprA, ligT, cinA, gyrB, and uvrB), dps1, genes homologous to plant desiccation resistance proteins, and genes for antioxidant proteins, chaperones, and proteases (645).…”
Section: Continued On Following Pagementioning
confidence: 99%
“…Our previous study revealed that the protein expression profile of E. coli harboring the irrE gene was significantly different from that of the control strain when challenged by NaCl. In total, 124 proteins including the osmotically inducible, detoxification and growth-related proteins, were differentially expressed (Pan et al 2009). Brassica napus is one of the most important oilseed crops cultivated worldwide, and it is sensitive to salt stress throughout the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Brassica napus is one of the most important oilseed crops cultivated worldwide, and it is sensitive to salt stress throughout the growing season. Our previous study showed that transgenic B. napus plants expressing the irrE gene can tolerate 350 mM NaCl (Pan et al 2009), a concentration that usually inhibits the growth of almost all crop plants, and the gene expression analysis of the transgenic irrE B. napus showed the gene encoding the plasma membrane Na ? /H ?…”
Section: Introductionmentioning
confidence: 99%
“…It can withstand extremely high doses of ionizing radiation, long periods of desiccation, UV radiation, and oxidizing agents and has a more efficient DNA repair system than any known species in the bacterial kingdom (12). The overexpression of IrrE (also named PprI), a global regulator of D. radiodurans that is essential for extreme radioresistance (13), has been reported to confer radiotolerance on E. coli (14), enhance salt tolerance in E. coli and Brassica napus (15), and improve osmoticstress tolerance in ethanologenic strains of E. coli, thereby increasing ethanol production (16). This global regulator has also been artificially engineered to improve tolerance to alcohols, such as ethanol and butanol (17), and inhibitors, such as furfural, hydroxyl methyl furfural, and vanillin, which are routinely observed in lignocellulosic hydrolysates used in biorefineries (18).…”
mentioning
confidence: 99%